CELEBRITY ENDORSER (BINTANG IKLAN) SEBAGAI KOMUNIKASI PEMASARAN TERHADAP KEPUTUSAN MEMBELI OLI FASTRON DI KOTA BALIKPAPAN - Abdiannur Abdiannur; Sukimin Sukimin (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2019)
Celebrity Endorser (visibility, credibility, attractiveness and power) towards the decision to buy fastron oil in Balikpapan City. The analytical tool used is multiple linear regression. The population in this research is all the use of fastron oil in Balikpapan City and the sample used is 100 respondents using purposive sampling technique. The results showed that the celebrity endorser variables (visibility, credibility, attractiveness, and power) simultaneously associated with Fastron oil purchasing decisions and partial variable visibility had a positive and significant effect, positive and significant credibility, positive and significant attractiveness and positive questionable power and significant to purchasing decisions and power variables are variables that have a dominant influence.